Comparison of Abiraterone and Combined Androgen Blockade Therapy for High-Risk Metastatic Hormone-Sensitive Prostate Cancer: A Propensity Score-Matched Analysis - Matsumura, Naoki; Fujita, Kazutoshi; Nishimoto, Mitsuhisa; Yamamoto, Yutaka; Kuwahara, Ken; Nagai, Yasuharu; Minami, Takafumi; Hatanaka, Yuji; Nozawa, Masahiro; Morimoto, Yasuhiro; Tahara, Hideo; Uejima, Shigeya; et al. (Frontiers in Oncology, 2021)
This study aimed to compare the effects of abiraterone acetate plus prednisone (AAP) with androgen deprivation therapy (ADT) with those of combined androgen blockade (CAB) therapy in patients with high-risk metastatic hormone-sensitive prostate cancer (mHSPC). This study retrospectively identified 163 patients with high-risk mHSPC at Kindai University and affiliated hospitals between January 2014 and December 2020. Kaplan-Meier analysis was used to summarize progression-free survival (PFS) and overall survival (OS). Multivariate Cox proportional hazard modeling was used to identify the prognostic factors in the overall cohort. Propensity score matching was used to adjust the clinical characteristics, and log-rank test was applied to these propensity score–matched cohorts. Seventy-four patients who received AAP with ADT and 89 patients who received CAB were included in this study. The median follow-up duration was 27 months (range, 2–89 months). The median PFS and OS were not reached by the AAP+ADT group and 15 and 79 months, respectively, in the CAB group. The Eastern Cooperative Oncology Group (ECOG) performance status (PS) score and AAP+ADT were significant prognostic factors for PFS, whereas ECOG PS score, visceral metastasis, and AAP+ADT were significant prognostic factors for OS. The 2-year PFS was 76.1% in the AAP+ADT group and 38.6% in the CAB group (P < 0.0001), and the 2-year OS was 90.2% in the AAP+ADT group and 84.8% in the CAB group (P = 0.015). Conclusions: AAP+ADT had better PFS and OS than CAB in patients with high-risk mHSPC.